QUALITY OF NET INTEREST INCOME OF INDONESIAN BANKS LISTED WITH INDONESIAN STOCK EXCHANGE DURING 2003-2006 - Ruhupatty, LeRoy Tim (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
The aim of this study is to determine the quality of net interest income recognized by Indonesian banks listed with the Indonesian Stock Exchange. The quality of net interest income is measured by its relationship with current cash flow from operation (CFO) and next year’s CFO. The findings indicate that net interest income is related to current operating income, related to current CFO, and related to next year’s CFO. These findings indicate that Indonesian banks listed with the Indonesian Stock Exchange report a high quality net interest income because they seemed to turn into cash flow from operation.